Rationality and the literate mind [ - Harris, Roy , 1931- (Routledge advances in communication and linguistic theory, 2009)
Examines the old debate about the relationship between rationality and literacy. This title challenges the received mainstream opinion that reason is an intrinsic property of the human mind, and argues that the whole Western conception of rational thought is a by-product of the way literacy developed in European cultures